Assessment of Nutritional Status in Children Attending Government Schools in Islamabad, A Cross Sectional Survey - Muhammad Inzamam Khalil, Khuday-E-Noor, Muhammad Irtizae, Luqman Nasir Idrees, Abdullah Asad, Anum Hussain Bibi, Amna Ahmad, Naima Irfan, Zille Huma Mustehsan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Child malnutrition is a major public health problem in most low income communities leading to high morbidity and mortality. According to National Nutrition Survey of Pakistan, 43% of children are stunted and 15% are wasted. Aim: To assess the nutritional status of the children attending the government schools in Islamabad. Methodology: A Descriptive cross-sectional survey was carried out on school going children 6-12 years of age (1st -5th grade) attending Islamabad Model School for Boys F.11/1, Islamabad. Sample Size of 80 was obtained by using Simple Random sampling. Data collection tools, weighing machine, height measuring tape, calculator and a questionnaire form containing socio-demographic data of a child (age, gender, height, weight, socioeconomic group etc.), BMI for age percentile growth chart and height age growth chart. Data analysis was done by using SPSS software version 23. Conclusion: Shorter heights of children may mask their poor nutritional status and deem them, to be healthy on a BMI scale. Economic, political and social changes should be made with special focus on mothers’ education to improve the nutritional status of children.